Modificação química do polipropileno através da introdução de grupos sulfônicos para aplicação como catalisador em reações de esterificação, visando a produção de biodiesel - Aud, Bárbara Nascimento (2022)
Surface functionalization of polymers is an alternative way to modify the hydrophilic/ hydrophobic character of a material. As a result of this process, it is possible to develop commercial polymers with new thermal, chemical and mechanical properties, increasing their applicability and with the possibility of using disposable materials. In this work, the chemical modification of pristine polypropylene (PP) was carried out through sulfonation reactions with concentrated sulfuric acid (98%), producing sulfonated polypropylene (PPS1), and with fuming sulfuric acid with 65% free SO3, producing the PPS2, which were used as heterogeneous catalysts in esterification reactions of oleic acid with methanol. For in relation to the synthesis of sulfonated polypropylene, a 3k factorial design was outlined, to maximize the efficiency of the reaction and to investigate the contributions of the variables of synthesis, time and polymer:sulfonating agent. The modified materials and the PP were characterized by spectroscopy in the infrared region (FTIR), elementary analysis (EA), scanning electron microscopy (SEM), X-ray diffraction (XRD), thermogravimetric analysis (TGA), differential scanning calorimetry (DSC) and ion exchange capacity measurements (IEC). The results showed that the two sulfonation agents were effective to promote the functionalization of PP, with the fuming sulfuric acid capable of promoting a greater chemical modification in the polymer. The evaluation of the modified materials as solid catalysts showed that both PPS1 and PPS2 have satisfactory catalytic activity in esterification reactions of oleic acid with methanol, showing even greater catalytic efficiency than the commercial ion exchange resin, Amberlyst 15. Under optimized conditions, the esterification catalyzed by PPS2, carried out at 100 °C, using 4% (w/w) of catalyst and alcohol:oleic acid molar ratio of 19.5:1, a conversion of 96.56% was obtained in 5 hours of reaction, while the process catalyzed by PPS1 provided a conversion of 84.86% in a reaction time of 3 hours, with alcohol:oleic acid molar ratio of 10:1, at 90 °C and a catalyst mass of 5% the starting oil. The reuse tests revealed that the materials, after acid regeneration, are structurally and catalytically stable even after 10 reaction cycles and can be recycled and reused without significantly reducing their activities. The kinetic study of the reactions catalyzed by PPS1 and PPS2 showed that the pseudo first order model fitted better to the experimental data, with an increase in reaction rate, in relation to the non-catalyzed process, of 58.51 and 44.91 times, respectively. Therefore, the results of this work showed that the conditions employed for the sulfonation of PP were satisfactory to produce materials with acidic characteristics necessary to catalyze the methyl esterification reaction of oleic acid, aiming at the production of biodiesel.